URGENSI PEMBATASAN ARTIFICIAL INTELLIGENCE (AI) DI SEKOLAH UNTUK MENCEGAH BRAIN ROT DAN COGNITIVE DEBT PADA SISWA - Yudha Saputra, Galih; Rahmadi; Hasbi Sjamsir; Fachrul Rozie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of Artificial Intelligence (AI) in education presents a dilemma between improving learning efficiency and the potential decline in students’ cognitive quality. Unregulated use of AI may trigger brain rot (decline in critical thinking ability) and cognitive debt (accumulated lack of understanding due to bypassing thinking processes). This study aims to analyze the urgency of restricting AI use in schools and to propose proportional strategies for its implementation in learning. The research employs a qualitative descriptive approach through literature review, analyzing relevant studies, educational policies, and conceptual frameworks on AI in education. The findings indicate that excessive AI usage reduces cognitive engagement, increases technological dependency, and promotes surface learning. Furthermore, without proper regulation, AI tends to replace essential thinking processes in students. Therefore, restricting AI use is a strategic necessity that should be implemented through developmentally appropriate approaches, risk-based regulation, process-oriented instructional design, and strengthened AI literacy. In conclusion, AI should not be prohibited but pedagogically controlled to ensure it functions as a supportive tool rather than a substitute for students’ cognitive processes.